ADVERTORIAL ELEKTRONIK PENGEMBANGAN BERBASIS WEB - , ZANNA CHOBITHA A, Mardhani Riasetiawan, S.E., Ak., M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The growth of commodity and services manufactures causes competition to acquire and retain customers. Marketing needs campaign medias as medium between manufactures and customers. Now, the promotion media still present in a conventional way which is unorganized well. It causes much trash and decreases the pleasure of society, especially the reader. Campaign medias require a variety of new innovations to produce targeted and interactive promotion. An alternative way of presenting an advertisement is through a media which is able to be used by the provider of good and service. This alternative way can be plugged in several media, like monitor, and can be put on the strategic and public locations. Development for commodities and services manufactures as a medium to support promotional activities are interactive media. Electronical advertorial is built using the object oriented programming concept, PHP programming language, CodeIgniter framework and MySQL database. Electronic advertorial success provides services such as advertising management, member management, advertising category management and showtimes management that equipped with the number of visitors in each served ads. Electronical advertorial supports the commodities and services manufacture to manage promotional activities through interactive media.